Antistatic base film and preparation method thereof

By using antistatic agents combined with polyether ester amide, tri-n-butyloctylphosphine bistrifluoromethanesulfonimide salt and polyethylene glycol monooleate in the antistatic base film, combined with modified inorganic particles and polyester materials, a multi-layer structural base film is designed to solve the problem that the existing antistatic base film is not permanent, and long-lasting antistatic properties, good optical properties and heat resistance are achieved.

CN119734504APending Publication Date: 2025-04-01江苏慧智新材料科技有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411948977.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing antistatic base films do not have permanent antistatic properties during storage, transportation and use, and are prone to accumulate electrostatic adsorption dust, affecting optical performance and heat resistance.

Method used

Antistatic agents combined with polyether ester amide, tri-n-butyloctylphosphine bistrifluoromethanesulfonimide salt and polyethylene glycol monooleate are used to improve antistatic and optical properties through the multi-layered base film design.

Benefits of technology

The long-lasting antistatic properties of the antistatic base film are achieved, while maintaining optical properties and heat resistance, avoiding the problems of electrostatic accumulation and dust adsorption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005214395250000071
    Figure BDA0005214395250000071
Patent Text Reader

Abstract

The invention discloses an antistatic base film, which comprises: a core layer sandwiched between a first surface layer and a second surface layer; the core layer, the first surface layer and the second surface layer are all made of polyester; the first surface layer and / or the second surface layer are / is an antistatic layer; and the antistatic layer also comprises the following raw materials: polyether ester amide, tri-n-butyl octyl phosphine bis (trifluoromethane sulfonimide) salt and polyethylene glycol monooleate. The antistatic base film is excellent in antistatic property persistence, and the optical property and the heat resistance of the base film are good. The invention also discloses a preparation method of the antistatic base film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of optical films, and in particular to an antistatic base film and a preparation method thereof. Background Art

[0002] Polyethylene terephthalate (PET) film has excellent mechanical properties and is widely used in optical base films. Due to its insulating properties, it is easy to accumulate static electricity and adsorb dust, causing the polyester film surface to become dirty, which can also lead to many destructive consequences. Film antistatic modification includes surface coating and internal addition. The former is to coat the film surface with an antistatic agent, which has a simple process flow, but it will fall off during storage, transportation and use, making the antistatic performance not permanent. The latter is to add conductive materials to the raw materials, but it is easy to be incompatible and agglomerate during mixing, and is also easy to migrate.

[0003] Therefore, it is necessary to improve the antistatic base film in the prior art. Summary of the invention

[0004] One of the purposes of the present invention is to overcome the defects in the prior art and provide an antistatic base film with excellent sustained antistatic performance and good optical properties and heat resistance.

[0005] In order to achieve the above process effects, the technical solution of the present invention is: an antistatic base film, comprising:

[0006] A core layer, sandwiched between the first surface layer and the second surface layer;

[0007] The materials of the core layer, the first surface layer and the second surface layer all include polyester;

[0008] The first surface layer and / or the second surface layer is an antistatic layer;

[0009] The raw materials of the antistatic layer further include polyether ester amide, tri-n-butyl octylphosphine bistrifluoromethanesulfonyl imide salt and polyethylene glycol monooleate.

[0010] The preferred technical solution is: the raw materials of the antistatic layer include 100 parts of polyester, 5-8 parts of polyether ester amide, 1-1.5 parts of tri-n-butyl octylphosphine bistrifluoromethanesulfonyl imide salt, and 1-3 parts of polyethylene glycol monooleate, calculated by weight.

[0011] The preferred technical solution is: the number average molecular weight of the polyethylene glycol monooleate is 400-600.

[0012] A preferred technical solution is: the material of the first surface layer and the second surface layer also includes modified inorganic particles, and the added amount of the modified inorganic particles is 0.1 to 1 part based on 100 parts of polyester.

[0013] The preferred technical solution is: the ratio of the thickness of the first surface layer, the core layer and the second surface layer is (5-6): (88-90): (5-6), and the total film thickness of the base film is 50-125 μm.

[0014] The second object of the present invention is to overcome the defects in the prior art and provide a method for preparing an antistatic base film, comprising the following steps:

[0015] S1: raw materials for preparing antistatic layer;

[0016] S2: The raw materials of the first surface layer, the core layer and the second surface layer are melted separately and cast into sheets;

[0017] S3: The molded casting is preheated for the first time, stretched longitudinally, and cooled for the first time;

[0018] S4: the longitudinally stretched cast sheet is sequentially subjected to a second preheating, heating and transverse stretching, heat setting and a second cooling to obtain the antistatic base film;

[0019] After the raw materials in S1 are dried, tri-n-butyloctylphosphine bistrifluoromethanesulfonyl imide salt is firstly mixed with polyether ester amide and polyethylene glycol monooleate for the first time, and then polyester is added for the second mixing.

[0020] The preferred technical solution is: the temperature of the first mixing is room temperature, and the mixing time is 3 to 5 minutes; the temperature of the second mixing is 250 to 260° C., and the mixing time is 2 to 3 minutes.

[0021] The preferred technical solution is: in S3, the first preheating temperature is 60-90°C, the longitudinal stretching temperature is 70-100°C, the longitudinal stretching ratio is 3-3.6 times, and the longitudinal stretching rate is 80-120 m / min;

[0022] In the S4, the second preheating temperature is 60-90°C, the transverse stretching temperature is 180-200°C, the transverse stretching ratio is 3-3.8 times, and the transverse stretching rate is 80-120 m / min.

[0023] The preferred technical solution is: the raw material melting of the core layer adopts a single screw, the temperature of the melt extruder is set to 180±2℃, 270±2℃, 280±2℃, 285±2℃, 285±2℃, 285±2℃, 285±2℃, 285±2℃, 285±2℃, 280±2℃ in sequence, and the temperature of the metering extruder is set to 270-280℃;

[0024] The raw material melting of the first surface layer and the second surface layer adopts a twin-screw, and the melting and metering are integrated. The extrusion temperatures are set to 290±2℃, 290±2℃, 285±2℃, 280±2℃, 275±2℃, 270±2℃, and 270±2℃ respectively.

[0025] The preferred technical solution is: the temperature of the heat setting is 220-240°C.

[0026] The advantages and beneficial effects of the present invention are:

[0027] The antistatic base film improves the durable antistatic property of the base film by using an antistatic agent composed of polyether ester amide, tri-n-butyl octylphosphine bistrifluoromethanesulfonyl imide salt and polyethylene glycol monooleate, while maintaining the optical property and heat resistance of the base film. DETAILED DESCRIPTION

[0028] The specific implementation of the present invention is further described below in conjunction with the examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, and cannot be used to limit the protection scope of the present invention.

[0029] The polyetheresteramide production unit is Arkema Group;

[0030] The production unit of tri-n-butyloctylphosphine bis(trifluoromethanesulfonyl)imide salt is Hunan Binghang New Materials Co., Ltd.;

[0031] The manufacturer of polyethylene glycol monooleate is Taizhou Jiayin Chemical Co., Ltd.;

[0032] The polyester is Sinopec FG600.

[0033] Antistatic layer

[0034] Polyetheresteramide is a polymer permanent antistatic agent, a block copolymer, composed of polyamide (PA, hard segment) and polyether (PEO, soft segment) alternating, combining the high strength and heat resistance of polyamide with the flexibility and low temperature performance of polyether. Its antistatic principle mainly relies on the ability of the polyether part to absorb or retain a certain amount of moisture, the strong mobility of the soft segment molecular chain, the easy movement of protons between molecules, and the conduction of static charge through the ether oxygen atoms in the chain segment, thereby increasing the conductivity of the material surface and helping to dissipate static charge. On the surface of the base film, it has a strip or layered structure. If the added content is too low, a conductive network cannot be formed. If the added content is too high, although the antistatic effect is improved, the poor compatibility with polyester leads to reduced mechanical properties of the base film and increased haze.

[0035] Tri-n-butyloctylphosphine bis(trifluoromethanesulfonyl)imide salt is an organic salt, which produces phase-separated micro-regions with polyester, allowing anions and cations to move freely in the polyester matrix to form a conductive path, and is compounded with polyetheresteramide to improve the antistatic properties of the base film.

[0036] The addition of polyethylene glycol monooleate not only further exerts the antistatic performance, but also improves the compatibility of tri-n-butyloctylphosphine bis(trifluoromethanesulfonyl)imide salt with polyester, and optimizes the transparency and haze of polyester. The hydrophilic group of polyethylene glycol monooleate combines with water molecules in the air to form a water film on the surface of the base film, and the lipophilic group is affinity with the organic salt, so that the antistatic composite material has a permanent antistatic effect. Furthermore, the number average molecular weight of polyethylene glycol monooleate is 400-600; if the number average molecular weight of polyethylene glycol monooleate is too large, its compatibility with polyester is poor, resulting in reduced mechanical properties of the base film and increased haze; if the number average molecular weight of polyethylene glycol monooleate is too small, its compatibility with polyester is improved, resulting in reduced phase separation micro-regions, resulting in the movement and restraint of anions and cations in the polyester matrix, and reduced antistatic performance.

[0037] Structure of antistatic base film

[0038] It is a single-sided antistatic film, wherein one of the first surface layer and the second surface layer is an antistatic layer, and the raw materials of the antistatic layer include polyester, modified inorganic particles, polyether ester amide, tri-n-butyl octyl phosphine bistrifluoromethanesulfonyl imide salt and polyethylene glycol monooleate; the raw materials of the other surface layer only include polyester and modified inorganic particles.

[0039] The double-sided antistatic film has a first surface layer and a second surface layer both being antistatic layers, and the raw materials of the antistatic layers include polyester, modified inorganic particles, polyether ester amide, tri-n-butyl octyl phosphine bistrifluoromethanesulfonyl imide salt and polyethylene glycol monooleate.

[0040] Modified Inorganic Particles

[0041] The inorganic particles in the modified inorganic particles are purchased from ABC NANOTECH Technology Co., Ltd. of South Korea. The modified inorganic particles are silica modified by a silane coupling agent, and the silane coupling agent is Dow Corning Z-6040 and / or Shin-Etsu KBM-503. The silica includes a first inorganic particle with a particle size of 10 to 120 nm and a second inorganic particle with a particle size of 0.5 to 5 μm, and the mass ratio of the first inorganic particle to the second inorganic particle is (0.3 to 1): 1. Furthermore, the mass ratio of the first inorganic particle to the second inorganic particle is (0.5): 1.

[0042] Example 1

[0043] The antistatic base film comprises a core layer, a first surface layer and a second surface layer, wherein the core layer is sandwiched between the first surface layer and the second surface layer, wherein the materials of the core layer, the first surface layer and the second surface layer all comprise polyester. It is a single-sided antistatic film, wherein the first surface layer is an antistatic layer, and the raw materials of the antistatic layer comprise 100 parts of polyester, 0.3 parts of modified inorganic particles, 6 parts of polyether ester amide, 1.2 parts of tri-n-butyl octylphosphine bistrifluoromethanesulfonyl imide salt, and 1.5 parts of polyethylene glycol monooleate by weight.

[0044] The preparation method of the antistatic base film comprises the following steps:

[0045] S1: preparing the raw materials for the antistatic layer. After the raw materials are dried, tri-n-butyloctylphosphine bistrifluoromethanesulfonyl imide salt is firstly mixed with polyether ester amide and polyethylene glycol monooleate for the first time, and then polyester is added for the second mixing. The temperature of the first mixing is room temperature and the mixing time is 4 minutes; the temperature of the second mixing is 256°C and the mixing time is 3 minutes.

[0046] S2: The raw materials for the first surface layer, the core layer and the second surface layer are melted separately and cast into sheets, wherein the raw materials for the core layer are melted by a single screw, and the temperatures of the melt extruder are set to 180°C, 270°C, 282°C, 285°C, 285°C, 285°C, 285°C, 285°C, 285°C, 280°C, respectively. The metering extruder has a total of nine zones, and the temperatures of each zone are 270°C, 270°C, 270°C, 270°C, 270°C, 270°C, 270°C, 270°C, 282°C, respectively; the raw materials for the first surface layer and the second surface layer are melted by a twin screw, and melting and metering are integrated. Modified inorganic particles are added together, and the extrusion temperatures are set to 290°C, 290°C, 285°C, 280°C, 275°C, 270°C, 270°C, and 270°C, respectively.

[0047] S3: The molded casting sheet is preheated for the first time at a temperature of 80°C, longitudinally stretched at a temperature of 88°C, a stretching ratio of 3.4 times, a stretching rate of 100 m / min, and cooled for the first time.

[0048] S4: The longitudinally stretched cast sheet was sequentially subjected to a second preheating temperature of 80°C, heating and transverse stretching at a temperature of 185°C, a stretching ratio of 3.6 times, a stretching rate of 110 m / min, a heat setting temperature of 230°C and a second cooling to obtain an antistatic base film.

[0049] The total thickness of the base film is 100 μm, the thickness of the first surface layer is 5.5 μm, the thickness of the core layer is 89 μm, and the thickness of the second surface layer is 5.5 μm.

[0050] Example 2

[0051] Example 2 is based on Example 1, except that, S1: in the raw materials for preparing the antistatic layer, the temperature of the second mixing is 290° C., and the mixing time remains unchanged. Other processes remain unchanged.

[0052] Example 3

[0053] Example 3 is based on Example 1, except that after the polyether ester amide and polyethylene glycol monooleate are mixed with polyester at 256°C for 3 minutes, tri-n-butyl octylphosphine bis(trifluoromethanesulfonylimide) is added for a second mixing, and the second mixing temperature is 256°C.

[0054] Comparative Example 1

[0055] Comparative Example 1 is based on Example 1, except that the raw materials of the antistatic layer include 100 parts of polyester, 0.3 parts of modified inorganic particles, 7.2 parts of tri-n-butyloctylphosphine bistrifluoromethanesulfonyl imide salt, and 1.5 parts of polyethylene glycol monooleate.

[0056] Comparative Example 2

[0057] Comparative Example 2 is based on Example 1, except that the raw materials of the antistatic layer include 100 parts of polyester, 0.3 parts of modified inorganic particles, 6 parts of polyether ester amide, and 1.2 parts of tri-n-butyl octylphosphine bistrifluoromethanesulfonyl imide salt.

[0058] Comparative Example 3

[0059] Comparative Example 3 is based on Example 1, except that the raw materials of the antistatic layer include 100 parts of polyester, 0.3 parts of modified inorganic particles, 7.2 parts of polyether ester amide, and 1.5 parts of polyethylene glycol monooleate.

[0060] Performance test of base film:

[0061] 1. Haze, transmittance and stability test

[0062] Instrument: AT-4725 transmission haze meter from BYK, Germany; Test standard: Tested according to ASTM D1003;

[0063] Five samples were taken from the obtained product polyester film, the sample size was 10*10 cm, and the sample cutting direction was consistent with the transverse and longitudinal directions of the polyester film. The haze value and transmittance of the five samples were measured using a transmission haze meter to obtain the average haze value H1 and the average transmittance value T1.

[0064] 2. Resistance value: According to ASTMD257 standard, use American TREK 152-1 surface resistance tester; test the resistance value of the base film surface in 70℃ environment for 24 hours to determine the aging resistance of the base film; after being placed at room temperature for 6 months, test the resistance value of the base film surface to determine its antistatic sustainability.

[0065] The measurement results of the embodiments and comparative examples are shown in the following table:

[0066]

[0067] Compared with Example 1, Example 2 uses high-temperature mixing, which easily leads to decomposition and re-esterification of the raw materials, thereby improving the compatibility between the raw materials. However, it restricts the free movement of anions and cations in the polyester matrix, and some antistatic raw materials are decomposed and ineffective.

[0068] Compared with Example 1, Example 3 has a negative impact on the antistatic properties, haze and transparency of the base film due to the fact that tri-n-butyloctylphosphine bis(trifluoromethanesulfonylimide) salt is an ionic liquid and uneven mixing occurs during the subsequent mixing.

[0069] Comparative Example 1 Compared with Example 1, the antistatic agent prepared by compounding polyether ester amide with tri-n-butyl octylphosphine bistrifluoromethanesulfonyl imide salt and polyethylene glycol monooleate has better antistatic performance and is more resistant to high temperature and aging.

[0070] Compared with Example 1, Comparative Example 2 does not contain polyethylene glycol monooleate, and the phase separation microregion of tri-n-butyloctylphosphine bis(trifluoromethanesulfonylimide) salt in the matrix is ​​large, and the compatibility is poor, which has a negative impact on the haze and transmittance of the base film and has a negative impact on the aging resistance.

[0071] Compared with Example 1, in Comparative Example 3, the content of polyetheresteramide is increased to form a strip or layered conductive network on the surface of the base film. Although the antistatic performance is improved, the haze and transparency of the base film are negatively affected.

[0072] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An antistatic base film, comprising: A core layer, sandwiched between the first surface layer and the second surface layer; The materials of the core layer, the first surface layer and the second surface layer all include polyester; The first surface layer and / or the second surface layer is an antistatic layer; The invention is characterized in that the raw materials of the antistatic layer further include polyether ester amide, tri-n-butyl octyl phosphine bistrifluoromethanesulfonyl imide salt and polyethylene glycol monooleate.

2. The antistatic base film according to claim 1, characterized in that: The raw materials of the antistatic layer include 100 parts of polyester, 5-8 parts of polyether ester amide, 1-1.5 parts of tri-n-butyl octylphosphine bistrifluoromethanesulfonyl imide salt, and 1-3 parts of polyethylene glycol monooleate in parts by mass.

3. The antistatic base film according to claim 1 or 2, characterized in that: The number average molecular weight of the polyethylene glycol monooleate is 400-600.

4. The antistatic base film according to claim 2, characterized in that: The material of the first surface layer and the second surface layer also includes modified inorganic particles. The added amount of the modified inorganic particles is 0.1 to 1 part based on 100 parts of polyester.

5. The antistatic base film according to claim 1, characterized in that: The thickness ratio of the first surface layer, the core layer and the second surface layer is (5-6): (88-90): (5-6), and the total film thickness of the base film is 50-125 μm.

6. A method for preparing an antistatic base film, characterized in that: The following steps are involved: S1: raw materials for preparing antistatic layer; S2: The raw materials of the first surface layer, the core layer and the second surface layer are melted separately and cast into sheets; S3: The molded casting is preheated for the first time, stretched longitudinally, and cooled for the first time; S4: the longitudinally stretched cast sheet is sequentially subjected to a second preheating, heating and transverse stretching, heat setting and a second cooling to obtain the antistatic base film; After the raw materials in S1 are dried, tri-n-butyloctylphosphine bistrifluoromethanesulfonyl imide salt is firstly mixed with polyether ester amide and polyethylene glycol monooleate for the first time, and then polyester is added for the second mixing.

7. The method for preparing the antistatic base film according to claim 6, characterized in that: The temperature of the first mixing is room temperature, and the mixing time is 3-5 minutes; the temperature of the second mixing is 250-260° C., and the mixing time is 2-3 minutes.

8. The method for preparing the antistatic base film according to claim 6, characterized in that: In S3, the first preheating temperature is 60-90° C., the longitudinal stretching temperature is 70-100° C., the longitudinal stretching ratio is 3-3.6 times, and the longitudinal stretching rate is 80-120 m / min; In S4, the second preheating temperature is 60-90° C., the transverse stretching temperature is 180-200° C., the transverse stretching ratio is 3-3.8 times, and the transverse stretching rate is 80-120 m / min.

9. The method for preparing the antistatic base film according to claim 6, characterized in that: The raw material melting of the core layer adopts a single screw, and the temperature of the melt extruder is set to 180±2℃, 270±2℃, 280±2℃, 285±2℃, 285±2℃, 285±2℃, 285±2℃, 285±2℃, 285±2℃, 280±2℃ in sequence, and the temperature of the metering extruder is set to 270-280℃; The raw material melting of the first surface layer and the second surface layer adopts a twin-screw, and the melting and metering are integrated. The extrusion temperatures are set to 290±2℃, 290±2℃, 285±2℃, 280±2℃, 275±2℃, 270±2℃, and 270±2℃ respectively.

10. The method for preparing the antistatic base film according to claim 6, characterized in that: The temperature of the heat setting is 220-240°C.

Citation Information

Patent Citations

  • Anti-electrostatic blue polyester film and preparation method therefor

    CN105219029A

  • Compound antistatic agent and preparation method thereof

    CN116356571A

  • Toughened antistatic polyformaldehyde material and preparation method thereof

    CN116656081A